2013
DOI: 10.1017/s0007114513002110
|View full text |Cite
|
Sign up to set email alerts
|

SEANUTS: the nutritional status and dietary intakes of 0.5–12-year-old Thai children

Abstract: In the present study, we investigated nutritional status and health-related factors in a multistage cluster sample of 3119 Thai urban and rural children aged 0·5-12·9 years. In a subsample, blood samples were collected for the measurement of Hb, transferrin receptor, vitamin A and vitamin D concentrations. The prevalence of stunting and underweight was higher in rural children than in urban children, whereas the wasting rate was similar in both rural and urban areas. Among children aged 3·0 -5·9 years, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 58 publications
12
103
4
1
Order By: Relevance
“…This study was part of the South East Asian Nutrition Survey (SEANUTS) which aimed to examine nutritional status and nutrient intakes of infants and children, aged 6 months -12 years, in Indonesia, Malaysia, Vietnam, and Thailand [16]. The survey in Thailand was carried out in four regions of the country during January-August 2011.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was part of the South East Asian Nutrition Survey (SEANUTS) which aimed to examine nutritional status and nutrient intakes of infants and children, aged 6 months -12 years, in Indonesia, Malaysia, Vietnam, and Thailand [16]. The survey in Thailand was carried out in four regions of the country during January-August 2011.…”
Section: Methodsmentioning
confidence: 99%
“…A recent nutrition survey in 3119 Thai infants and children, aged 6 months -12 years, from 4 regions of Thailand including Bangkok, showed an overall prevalence of childhood obesity of 11.8% for municipal and 5.9% for non-municipal areas and the highest proportion of obese children was found among the school-age group (6 to 12 years). The prevalence of underweight ranged between 6.4% -10.2% and the stunting prevalence in non-municipal areas was twice as high as in municipal areas; 8.4% versus 4.1% [16]. Furthermore, results showed that calcium, iron and vitamin C intakes of children were relatively low compared to the recommendation [16].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data on nutrient intakes and biochemical status in young children aged 12-36 months from 19 countries were reviewed by the expert group [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. They are obtained from both national surveys and cross-sectional community-based surveys in Asia (Bangladesh, India, Indonesia, Malaysia, People's Republic of China, Philippines, Thailand and Vietnam), Australia, New Zealand, Europe (France, Ireland and Norway), Africa (Cameroon and South Africa), North America (Canada, Mexico and USA) and South America (Brazil).…”
Section: Nutrient Intakes and Status Of Young Children Aged 12-36 Monthsmentioning
confidence: 99%
“…The sampling procedures followed in each one of the four SEANUTS countries are described in detail elsewhere (17,(19)(20)(21)(22) . In brief, both Indonesia and Thailand used population-based sampling approaches, whereas Malaysia and Vietnam performed their sampling in nurseries, kindergartens and primary schools.…”
Section: Samplingmentioning
confidence: 99%